2016
DOI: 10.1002/ange.201605259
|View full text |Cite
|
Sign up to set email alerts
|

Die Chemie von [AuO]+/CH4 in der Gasphase: Selektive Sauerstoffatom‐Übertragung auf, statt Wasserstoffatom‐Abstraktion von Methan

Abstract: Die thermischen Reaktionen von [AuO] + mit Methan wurden mittels FT-ICR-Massenspektrometrie und quantenchemischenRechnungen untersucht. Im Gegensatz zu den bereits untersuchten Oxiden der 11. Gruppe,[CuO] + und [AgO] + ,r eagiert [AuO] + mit CH 4 ausschließlich unter Bildung von CH 3 OH durchS auerstoffatomübertragung.D er neuartige Mechanismus dieser spezifischen Oxidation wird vorgestellt und die Ursachen der Trägheit des [AgO] + /CH 4 -Reaktionspaares mittels theoretischer Untersuchungen aufgedeckt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…A variety of 1-(hydroxy) alkyltrifluoroborates have been prepared from the corresponding aldehydes through a Cu-catalyzed diboration protocol employing ICyCuCl (ICy ¼ 1,3-dicyclohexylimidazol-2-ylidene) (Scheme 36) [73]. The developed method, which was based on a previously reported aldehyde diboration protocol [74], allows isolation of air-stable trifluoroborate salts upon quenching with KHF 2 . It was demonstrated that substrates bearing alkenes as well as protected alcohols and amines could be successfully prepared.…”
Section: Enantioselective C-c Bond Formationmentioning
confidence: 99%
“…A variety of 1-(hydroxy) alkyltrifluoroborates have been prepared from the corresponding aldehydes through a Cu-catalyzed diboration protocol employing ICyCuCl (ICy ¼ 1,3-dicyclohexylimidazol-2-ylidene) (Scheme 36) [73]. The developed method, which was based on a previously reported aldehyde diboration protocol [74], allows isolation of air-stable trifluoroborate salts upon quenching with KHF 2 . It was demonstrated that substrates bearing alkenes as well as protected alcohols and amines could be successfully prepared.…”
Section: Enantioselective C-c Bond Formationmentioning
confidence: 99%
“…For decades, ion/molecule reactions (IMRs) of mass-selected ions A + and neutral molecules B conducted in the dilute gas phase constitute a powerful method to investigate the elementary steps of chemical reactions. [1][2][3][4][5][6][7][8][9][10][11][12][13] CÀ H-bond activation, [5,[14][15][16][17][18] oxygen-atom transfer, [19][20][21] and the concept two-state reactivity [22][23][24][25][26][27] are just a few out of many examples. While the operational details of IMRs vary for different experimental setups (e. g. triple-quadrupole mass spectrometers, [28][29][30] ICR mass spectrometers, [31][32][33][34][35] quadrupole ion-traps [28,[36][37][38][39][40][41][42] ), the general sequence of steps starts with the encounter of the ion A + and the neutral molecule B to form a charged adduct complex AB + (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] The good control over the cluster size, composition and charge state allows to distinguish the effects of these parameters on the studied reactions. Moreover, the highvacuum conditions of a gas-phase experiment eliminate the contaminating agents that could affect the reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Small clusters in the gas phase have proven to be ideal model systems for investigating the fundamental aspects of complex reactions . The good control over cluster size, composition, and charge state allows the effects of these parameters on the studied reactions to be distinguished.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation